Predictive value of ferritin heavy chains in the development of coronary artery calcification in patients on maintenance hemodialysis: a prospective cohort study - Chen, Sipei; Tang, Yu; Pu, Yangmei; Xia, Xiaoqiang; Li, Yi; Zou, Yang (Frontiers in Endocrinology, 2025)
BackgroundVascular calcification (VC) is a well-established risk factor for cardiovascular disease (CVD) and mortality in patients on maintenance hemodialysis (MHD). These patients frequently present with hyperphosphatemia as well as disorders of iron metabolism. This study aims to explore the role of ferritin heavy chain (FTH) in the development and progression of coronary artery calcification (CAC) in patients on MHD and assess its predictive value.MethodsUsing a bioinformatics approach, we analyzed datasets related to VC. In our prospective study, we evaluated the Coronary Artery Calcification Score (CACS) alongside clinical markers, including serum FTH, serum ferritin, and transferrin saturation (TSAT), in patients on MHD at baseline and after a 1-year follow-up.ResultsFth1 was identified as a differentially expressed gene significantly upregulated in the aorta of both ApoE-/- mice (atherosclerotic calcification model) and chronic kidney disease (CKD) mice (medial calcification model). Among patients on MHD, 85.71% exhibited CAC, with 49.09% showing progression. Patients with CAC tended to be older and have a higher body mass index (BMI). Notably, serum FTH and phosphorus (P) levels were significantly elevated in those with progressive CAC. Elevated serum FTH and high serum P were both independent risk factors for CAC progression and showed predictive value.ConclusionElevated serum FTH and high serum phosphorus are clinically significant predictors of VC progression in patients on MHD.